Discrete limit theorems for Estermann zeta-functions. II - Laurincikas, A.; Macaitiene, R. (Algebra and Discrete Mathematics, 2008)
A discrete limit theorem in the sense of weak convergence of probability measures in the space of meromorphic functions for the Estermann zeta-function with explicitly given the limit measure is proved.